1991
DOI: 10.1093/milmed/156.8.430
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aspects of Familial Multiple Myeloma

Abstract: To elucidate the role of genetics in familial multiple myeloma, two sisters having plasma cell dyscrasia were studied. The women were 58 and 56 years old, and the diagnoses were made 22 months apart. Specific antisera for patient 1's lambda light chains produced in rabbits had no cross-reactivity with her sister's lambda light chains. Karyotypic analysis by G.T.G. banding revealed abnormalities in both patients, but no common abnormalities. HLA typing disclosed identical tissue types (AW24, A26, B13, BW55). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Patients with congenital immunodeficiency syndromes, such as Chediak–Higashi syndrome, ataxia‐telangectasia, B‐cell lymphoproliferative syndrome, Bruton agammaglobulinemia, common variable immunodeficiency, and Wiscott–Aldrich syndrome, are known to be predisposed to lymphoma 1–4. Apart from these syndromes, familial aggregation of lymphoma has been reported repeatedly,1–3, 8–20 but few population‐based studies have been published. Some authors have proposed an autosomal dominant transmission of lymphoma,2, 6 but in most families the pattern of transmission is unclear.…”
mentioning
confidence: 99%
“…Patients with congenital immunodeficiency syndromes, such as Chediak–Higashi syndrome, ataxia‐telangectasia, B‐cell lymphoproliferative syndrome, Bruton agammaglobulinemia, common variable immunodeficiency, and Wiscott–Aldrich syndrome, are known to be predisposed to lymphoma 1–4. Apart from these syndromes, familial aggregation of lymphoma has been reported repeatedly,1–3, 8–20 but few population‐based studies have been published. Some authors have proposed an autosomal dominant transmission of lymphoma,2, 6 but in most families the pattern of transmission is unclear.…”
mentioning
confidence: 99%
“…Law (1976) and Manigand et al (1970) reported that the karyotypic analysis in the pairs of patients was normal. Loth & Perotta (1991) demonstrated chromosome abnormalities for both patients, but there were no common abnormalities. In the present study, only one chromosome abnormality (loss of the X chromosome) was found.…”
Section: Discussionmentioning
confidence: 85%
“…In familial multiple myeloma we have described previously (Grosbois et al , 1986) an HLA identity in two brothers. Loth & Perrotta (1991) also reported HLA identity in two sisters. In the present study we found one case of immunogenetic identity in two sisters.…”
Section: Discussionmentioning
confidence: 90%
“…Familial clustering of MM has been reported only relatively recently [116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] (reviewed by Lynch et al [134]). There have been 53 reported instances of MM occurring in more than one family member, with four of these families each having three or more siblings affected with MM [119,124,130,134].…”
Section: Multiple Myelomamentioning
confidence: 99%